2011
DOI: 10.1093/cid/cir230
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Initiation of Antiretroviral Therapy in Human Immunodeficiency Virus (HIV)-Associated Tuberculous Meningitis

Abstract: Immediate ART initiation does not improve outcome in patients presenting with HIV-associated tuberculous meningitis. There were significantly more grade 4 adverse events in the immediate ART arm, supporting delayed initiation of ART in HIV-associated tuberculous meningitis. Clinical Trials Registration. ISRCTN63659091.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(174 citation statements)
references
References 20 publications
4
160
1
4
Order By: Relevance
“…Here we report clinical outcomes among hospitalized Ugandans treated for TB meningitis over a 6.5-year period. In-hospital mortality was high in the cohort overall (44%), similar to other research settings with high HIV prevalence 7, 19, 22, 23 . The adjusted model on imputed data found odds of in-hospital mortality were almost two fold higher in the earliest cohort, tested by CSF smear microscopy only, than that of that of the most recent cohort in whom Xpert (and culture) are routinely performed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Here we report clinical outcomes among hospitalized Ugandans treated for TB meningitis over a 6.5-year period. In-hospital mortality was high in the cohort overall (44%), similar to other research settings with high HIV prevalence 7, 19, 22, 23 . The adjusted model on imputed data found odds of in-hospital mortality were almost two fold higher in the earliest cohort, tested by CSF smear microscopy only, than that of that of the most recent cohort in whom Xpert (and culture) are routinely performed.…”
Section: Discussionsupporting
confidence: 84%
“…However for pulmonary TB, Xpert has not been shown to decrease mortality 1618 . Yet, lessening diagnostic delay in persons with TBM may be more likely to lead to improved outcomes as compared to pulmonary TB given the high early mortality of TBM 19 . Whether routine use of Xpert for investigation of suspected TBM has made an impact on mortality has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with pulmonary TB early ART initiation is associated with improvements in AIDS-free survival, particularly in patients with low baseline CD4 counts 27 . In patients with HIV-associated TBM, however, our previous study suggested that immediate ART did not result in a survival benefit, but was associated with an increase in severe adverse events 28 . The current study aimed to investigate the effect of ART initiation time upon drug exposures both in the systemic circulation and the CNS, and to assess if drug exposure correlated with clinical outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…The study participants were HIV-infected adults (aged > 15 years) who fulfilled diagnostic criteria for TBM. Baseline demographic clinical and laboratory features of the study participants are reported elsewhere 28 . Rich pharmacokinetic data This article is protected by copyright.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation